Water-based 2-dimensional anatase TiO2 inks for printed diodes and transistors. Issue 12 (7th March 2023) - Kassem, Omar; Pimpolari, Lorenzo; Dun, Chaochao; Polyushkin, Dmitry K.; Zarattini, Marco; Dimaggio, Elisabetta; Chen, Liming; Basso, Giovanni; Parenti, Federico; Urban, Jeffrey J.; Mueller, Thomas; Fiori, Gianluca; et al.
Abstract : TiO2 nanosheets are produced with a mass scalable and F-free bottom-up approach. The material is formulated into a stable water-based ink and exploited in printed diodes and transistors, showing very good dielectric properties. Abstract : 2-Dimensional (2D) materials are attracting strong interest in printed electronics because of their unique properties and easy processability, enabling the fabrication of devices with low cost and mass scalable methods such as inkjet printing. For the fabrication of fully printed devices, it is of fundamental importance to develop a printable dielectric ink, providing good insulation and the ability to withstand large electric fields. Hexagonal boron nitride (h-BN) is typically used as a dielectric in printed devices. However, the h-BN film thickness is usually above 1 μm, hence limiting the use of h-BN in low-voltage applications. Furthermore, the h-BN ink is composed of nanosheets with broad lateral size and thickness distributions, due to the use of liquid-phase exfoliation (LPE). In this work, we investigate anatase TiO2 nanosheets (TiO2 -NS), produced by a mass scalable bottom-up approach. We formulate the TiO2 -NS into a water-based and printable solvent and demonstrate the use of the material with sub-micron thickness in printed diodes and transistors, hence validating the strong potential of TiO2 -NS as a dielectric for printed electronics.